Program Pengabdian Masyarakat: Metode Pembenah Tanah melalui Kombinasi Biochar Abu Sekam dan Bakteri Bacillus sp. di Lahan Sawah Poktan Karya Tani Desa Kertosari - Maharani, Marcellia; Pratama, Sandy Yoga; Ardian Isa Fahrezi; Fajriansyah Aulia Firdaus; Afhinka Faza Naulia; Andini Dwi Fitriana; Ulfatul Islamiyah; Isna Khilbasa Mas’ula; Vivi Fitriani; Della Puspita; Adelia Putri Karinda (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Kertosari Village, Pakusari District, Jember Regency is one of the regions with relatively high rice productivity. One of the farmer groups in the village is Poktan Karya Tani who manages rice fields while also running a side business in the form of the brick industry. Community service activities aim to:increase the capacity of farmers to utilize local waste, a useful product in the form of a biofertilizer combined with biochar such as husk and bacillus sp. Community service consists of a series activities including outreach, training in making biochar, and application biochar. Socialization activities can increase farmers' knowledge regarding the importance of using biological fertilizers in combination with husk ash biochar. Based on the results of the comparison of pretest scores and posttest, there was an increase in farmers' understanding with an average of around 60% - 90%. increased to 100% after socialization was carried out. Potassium levels increased after applying a biological fertilizer combination of husk ash biochar and bacillus sp. Soil potassium levels reached 3.13 me/100g and continued to increase higher after 4 weeks, reaching 6.10 me/100g in the very high category. Fe levels in the soil also decreased from 1.3 ppm to 0.5 ppm.